2021
DOI: 10.1093/femsle/fnab029
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and accurate method for screening T-2 toxin in food and feed using competitive AlphaLISA

Abstract: T-2 is a common mycotoxin contaminating cereal crops. Chronic consumption of food contaminated with T-2 toxin can lead to death, so simple and accurate detection methods in food and feed are necessary. In this paper, we establish a highly sensitive and accurate method for detecting T-2 toxin using AlphaLISA. The system consists of acceptor beads labeled with T-2-bovine serum albumin (BSA), streptavidin-labeled donor beads, and biotinylated T-2 antibodies. T-2 in the sample matrix competes with T-2-BSA for anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The contamination rates of this toxin in feedstuffs or field crops in various regions have been reported in previous studies [10]. General signs of T2 toxicity in animals include weight loss, feed refusal, vomiting, rash, bleeding, diarrhea, and even death [11]. It has been universally confirmed that persistent exposure to T2 causes anabrosis and necrosis of oral and intestinal mucosa in pigs, leading to vomiting, diarrhea, reduction in feed intake, and other effects, such as immunotoxicity [12].…”
Section: Introductionmentioning
confidence: 69%
“…The contamination rates of this toxin in feedstuffs or field crops in various regions have been reported in previous studies [10]. General signs of T2 toxicity in animals include weight loss, feed refusal, vomiting, rash, bleeding, diarrhea, and even death [11]. It has been universally confirmed that persistent exposure to T2 causes anabrosis and necrosis of oral and intestinal mucosa in pigs, leading to vomiting, diarrhea, reduction in feed intake, and other effects, such as immunotoxicity [12].…”
Section: Introductionmentioning
confidence: 69%
“…For AlphaLISA detection system, the right proportions of acceptor beads, biotin-labeled antibody, and donor beads are needed to maximize its sensitivity and specificity ( 13 , 14 ). Based on our previous experience, concentrations of 62.5 μg/mL and 100 μg/mL of horse polyclonal antibody coupling acceptor beads, 0.5 μg/mL and 1 μg/mL of biotinylated monoclonal antibody, and 25 ug/ml, 33.3 μg/mL, and 40 μg/mL of streptavidin donor beads were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the short lifespan of singlet oxygen in solution, the background signal of this method is relatively low. From our previous research on this method ( 13 , 14 ), we found that matrix interference was relatively low. We evaluated the efficacy of this detection method on botulism contaminated samples by testing a wider range of sample types.…”
Section: Introductionmentioning
confidence: 90%
“…The contamination rates of this toxin in feedstuffs or eld crops in various regions have been reported in previous studies [9]. General signs of T2 toxicity in animals include weight loss, feed refusal, vomiting, rash, bleeding, diarrhea, and even death [10]. It has been universally con rmed that persistent exposure to T2 causes anabrosis and necrosis of oral and intestinal mucosa in pigs, leading to vomiting, diarrhea, reduction in feed intake, and other effects, such as immunotoxicity [11].…”
Section: Introductionmentioning
confidence: 83%